IMPLEMENTASI PENYERAHAN DATA DOKUMEN NASABAH TERHADAP PEDAGANG VALUTA ASING BUKAN BANK (STUDI KASUS: P.T. RASYA JAYA SEJAHTERA) - Bunga Wahyuni, Ivana; Wiryawan, I Wayan; Sri Indrawati, Anak Agung (Kertha Semaya : Journal Ilmu Hukum, 2015)
The implementation of handover documents data customers to foreign currencytrader non-bank. Company in doing their business activity is obliged to get the protectionlaw. The applications restrict transactions with the limits higher through the handoverdocument data customers at odds with the law - The regulations limited company to gainany profit. The purpose of this writing, to analysis Bank Indonesia regulation in foreigncurrency traders identified customer non-bank in P.T. Rasya Jaya Sejahtera. The methodsused in this writing as empirical judicial with approaching problems from based on rulesand regulation as approach. From research in, found results the implementation fromIndonesian central bank’s policy experienced profit benefits company P.T. Rasya JayaSejahtera.
Keywords: Implementation, Documents, Customers, Forreign Currency